Causes of visual impairment and blindness in children in three ecological regions of Nepal: Nepal Pediatric Ocular Diseases Study - Adhikari S; Shrestha MK; Adhikari K; Maharjan N; Shrestha UD (Clinical Ophthalmology, 2015)
Srijana Adhikari,1 Mohan K Shrestha,1 Kamala Adhikari,2 Nhukesh Maharjan,1 Ujjowala D Shrestha1 1Pediatric Ophthalmology unit, Tilganaga Institute of Ophthalmology, Gaushala, Kathmandu, Nepal; 2Private consultant, Kathmandu, Nepal Purpose: To study the causes of blindness and visual impairment in children in three ecologically diverse regions of Nepal.Materials and methods: This is a baseline survey report of a 3-year longitudinal population-based study. One district each from the three ecological regions – Terai, Hills, and Mountains – was selected for the study. Village Development Committees from each district were selected by random sampling. Three community health workers were given training on vision screening and identification of abnormal ocular conditions in children. Health workers who examined children and collected data using pretested questionnaire performed house-to-house surveys. Children with abnormal vision or ocular conditions were referred to and examined by pediatric ophthalmologists.Results: A total of 10,950 children aged 0–10 years, 5,403 from Terai, 3,204 from Hills, and 2,343 from Mountains, were enrolled in the study. Of them, 681 (6.2%) were nonresponders. The ratio of boys to girls was 1.03:1. Prevalence of blindness was 0.068% (95% confidence interval [CI] 0.02%–0.12%) and visual impairment was 0.097% (95% CI 0.04%–0.15%). Blindness was relatively more prevalent in Terai region (0.08%, 95% CI 0.02%–0.13%). The most common cause of blindness was amblyopia (42.9%) followed by congenital cataract. Corneal opacity (39%) was the most common cause of unilateral blindness.Conclusion: More than two-thirds of the causes that lead to blindness and visual impairment were potentially preventable. Further, nutritional and genetic studies are needed to determine the factors associated with ocular morbidity and blindness in these regions. Keywords: vision screening, ocular morbidity, childhood, Nepal, pediatric